Analisis Pengaruh Procedural Fairness, Distributive Fairness, Interactional Fairness, Trust dan Satisfaction terhadap Continuance Intention In Online Shopping - Andy, Andy; Purwianti, Lily (Journal of Accounting and Management Innovation, 2017)
Flourishing of internet has made all industries engage in this particular medium as part of globalization. Due to the internet digital format and ability to make communication with people across the globe, electronic commerce is now one of the main source of opportunity in business nowadays. In Indonesia, many entrepreneurs and small scale business take advantage of internet to run online business including business to consumer and business to business.Â  The goal of this study is to explore customer intention in continue online shopping as the success depends on fairness, trust and user satisfaction. Online shopping involves higher levers of uncertainty than visiting actual shop as online shopping lacks the information and physical assurance so the fairness and trust play a very important role in online shopping. In this study, our respondents are university students in Batam city as students are the largest internet user compared to other professional. We use non purposive with purposive sampling method and this kind of data analysis are simple regression and multiple regression.Â  This study conclude that fairness, and satisfaction play a significant effect to satisfaction. Satisfaction itself have a significant effect to continuance intention in online shopping. Key Words : Marketing strategies, Online store, Fairness, Trust , Satisfaction.